2010
DOI: 10.5432/ijshs.20090033
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Electrical Muscle Stimulation Attenuates Postprandial Hyperglycemia in Obese and Pre-obese Japanese Men

Abstract: The present study aimed to examine whether a single bout of percutaneous low-frequency electrical muscle stimulation (EMS) can attenuate postprandial hyperglycemia in human subjects. Ten obese and 4 pre-obese Japanese men participated in two experimental sessions; one involved 20 min of EMS just after a breakfast (EMS trial) and the other involved complete rest after a breakfast (Control trial). In each trial, blood samples were taken before and at 30, 60, 90, and 120 minutes after the meal. Blood lactate conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…The results showed that the postprandial glucose levels were lower in the MES trial than the control trial [14]. In our study, the MES potency did not appear to be high enough to increase glucose uptake in the skeletal muscle.…”
Section: Oxygen Consumption (Vo2)contrasting
confidence: 61%
“…The results showed that the postprandial glucose levels were lower in the MES trial than the control trial [14]. In our study, the MES potency did not appear to be high enough to increase glucose uptake in the skeletal muscle.…”
Section: Oxygen Consumption (Vo2)contrasting
confidence: 61%
“…NMES is thought to preferentially recruit different motor units in position and in type. 25 Kimura et al 15 has argued the potential benefits in type 2 diabetes of a higher proportion of type IIb fibres being exercised. If a person both walks and uses this modality, then there will be a different fibre mix recruited by each exercise type and the total proportion of fibres exercised will be higher.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Even traditional NMES techniques exercising at just two metabolic equivalents (oxygen consumption of 7 ml/kg/min) has been shown to enhance total body glucose uptake and attenuate postprandial hyperglycemia in the obese. 15 The therapeutic potential of traditional NMES on diabetes has been investigated previously with no improvement in haemoglobin A1c (HbA1c) or insulin sensitivity. 16 However, as a traditional NMES system was used, this had little physiological impact on study participants, for example, there was only a 9% increase in energy expenditure above baseline values.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, standard exercise regimes are insufficiently appealing to the many who could but do not regularly exercise (Varo et al 2003) and the present NMES protocol could be an alternative. Moreover, it has recently been shown that an NMES protocol may also attenuate postprandial hyperglycemia in obese male participants (Kimura et al 2010). Thus NMES techniques may emerge as a potential alternative exercise method for overweight participants and people with diabetes.…”
Section: Discussionmentioning
confidence: 99%